Strategi Peningkatan Kedisiplinan Aparat Desa Dalam Meningkatkan Mutu Pelayanan - Aminatus Sholikah Putri; Lalu Satria Utama (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2024)
This article presents information on strategies for improving the discipline of village officials as an effort to enhance the quality of services at the local level. The main objective of this study is to analyze and improve the discipline of village officials as a key factor that can contribute to the improvement of public service quality. The rationale for conducting this research is related to the issues of discipline that can affect the effectiveness and efficiency of public services at the village level. Improving discipline is expected to optimize the potential of village officials in providing responsive and high-quality services to the community. The research methodology used involves both qualitative and quantitative approaches with data collection through interviews, observations, and document analysis. In addition, surveys and literature studies were conducted to strengthen the conceptual framework of the research. The findings of this study indicate that the implementation of strategies to improve discipline, such as training, supervision, and coaching, can significantly enhance the quality of services provided by village officials. Factors affecting discipline, such as motivation and managerial support, were also identified as important elements in achieving optimal results.